The sport of kings : - Cassidy, Rebecca (Cambridge University Press, 2002)
This unique "behind the scenes" description of British flat racing is based on first hand experiences in Newmarket, the Suffolk town regarded as the international headquarters of the sport. Cassidy offers an insider's look at the rituals of horseracing--including those on the racecourse and at the bloodstock auction--and shows how racing, betting and the bloodstock industry are connected. Her insightful descriptions of the class structure of Newmarket explain how racing professionals preserve both the sport and their status quo.